Comparative Study of the Application of Blended Learning Method Versus Face-to-Face Learning Method in Student Learning AchievementCase Study: Computer Graphic Courses at Widyatama University - Ovyawan Herlistiono, Iwa; Violina, Sriyani (International Journal of Psychosocial Rehabilitation, 2020)
The e-learning method does not require face-to-face interaction between teachers and students; all teaching and learning activities are bridged by the e-learning system. At the time of implementation, there were several obstacles to the implementation of e-learning, including inadequate infrastructure and an independent learning culture that students did not yet have that still required face-to-face activities with the instructor. Blended learning is a learning method that combines e-learning systems with face-to-face methods. In 1 (one) semester, it is determined when learning is done by an e-learning system and when it is done face-to-face. This study compares student learning outcomes using face-to-face and blended learning methods for Computer Graphic courses at Widyatama University